Pentingnya Keterampilan Retorika Da’i di Era Society 5.0 dalam Efektivitas Keberhasilan Dakwah Kepada Mad’u - Umi, Khofifah (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2023)
The era of society 5.0 is an era where almost all human work is assisted by sophisticated machines or technology that makes it easier for humans to do their jobs. In this era of all-technology, preachers are required to have rhetorical skills and a qualified ability to use technology as a medium in conveying tausyiah or da'wah to mad'u. Skills in using technology will pave the way for preachers to be more flexible in conveying their da'wah without fear of being limited by space and time. Da'wah skills on social media can take the form of interesting writing or videos that make mad'u interested in reading and watching what the preachers convey where this is the key to how effective the da'wah delivered to mad'u is. Keyword :Era of society 5.0, skills, effectiveness